Perfil do controller e escolhas estratégicas: uma análise qualitativa à luz da Teoria dos Altos Escalões - Ferreira, Mônica Aparecida (2021)
Over the years, there has been some discussions on the different roles that the controller occupies in organizations and the current one consists of the dichotomy of the role of controllers as bean-counters, which corresponds to those centered on the production of information that assist the management process, or as business partners, who are involved in the company's management process and other organizational areas, being considered true business partners. It is understood that the controller makes up the top echelon, once its main function is to contribute to good organizational performance. When talking about the high echelons, we have the Upper Echelons Theory, which seeks to explain the organizational strategies and the performance of organizations based on the analysis of the personal characteristics of those who participate in the management process of the entity. Thus, the objective of this research is to understand how the values and the cognitive basis, proposed by Upper Echelons Theory, are perceived in the strategic choices of the controller in companies operating in Brazil and Portugal. Therefore, a qualitative research was carried out, with an interpretive research paradigm. Two case studies and interviews were conducted with controllers and ex-controllers from different organizations, with different business realities in both countries: Brazil and Portugal. The method used in this research is shadowing and to complement the analysis, the sources were triangulated through interviews and document collection. The innovation of the research is to examine personal characteristics, from the perspective of values and the cognitive basis in a qualitative approach in the field of research considering the controller. The results show that previous professional experience and academic training are perceived in the strategic choices made by the controllers investigated in both countries. Regarding academic training, it is clear that peculiar aspects of the two countries are decisive, and in Brazil training in Accounting was predominant, while in Portugal training in Management and other courses stood out. The results also point out that the values of collectivism, rationality, duty and innovation stood out as expected values for exercising the role of controller; materialism and power were less present. It was possible to observe that the functions and strategic choices in which each controller engages depends on the profile of that controller (personal characteristics), but also on the way that the organizational environment is hierarchically structured, on the organizational culture, on the level of autonomy that the high echelon gives this professional and even the characteristics of high-level members who are at the head of the company, besides the specificities of each country. Thus, this research contributes in a theoretical way to expand the field of application of Upper Echelons Theory, mainly by investigating more subjective aspects of the performance of managers and strategic choices. It contributes in a practical way to companies in the organizational structuring of the management process, aligning the controller's profile and the organizational objectives.